3D Into 5E for Space Sciences Lessons Using NASA Education Resources for Elementary and Middle School Classrooms - Lee, Soon; Bergman; Novacek (Innovations in Science Teacher Education, 2023)
Implementation of the Next Generation Science Standards (NGSS; NGSS Lead States, 2013) 3D learning that is well aligned with the performance expectations has been challenging for many science teachers. Furthermore, studies on curriculum materials for NGSS have rarely provided templates or guidelines that are straightforward for teachers to use in their science classes. This project aimed to provide professional development opportunities to middle school teachers (Grades 5–8) through a workshop designed to facilitate the integration of NASA’s educational resources into science lessons aligned with the NGSS 3D learning framework. The workshop included a conceptual model (i.e., 3D Into 5E), lesson templates, and sample lessons. Specifically, the project activities were designed to improve the participating teachers’ space-science content knowledge and instructional strategies, thereby enabling them to capture their students’ interest and channel it toward related STEM careers. Although the BSCS 5E Instructional Model (Bybee et al., 2006) is not a new concept, this project has demonstrated its efficacy as a template for effectively integrating the three dimensions of NGSS with related phenomena in science teaching. This project has not only demonstrated the effectiveness of the 5E model as a tool for promoting a deeper understanding of scientific concepts but also innovatively incorporated hands-on space-science activities to enhance its impact. By engaging teachers in these activities, the project improved their ability to modify instructional materials using the 3D Into 5E template, ultimately leading to a more engaging and impactful learning experience for their students. The study’s results showed that participating teachers experienced significant improvements in their space-science content knowledge and teaching confidence, indicating the effectiveness of this innovative approach. The teachers also reported high levels of student engagement and enjoyment during space-science activities, indicating the potential of this approach to enhance student-centered learning and improve the quality of science instruction delivered to students. Overall, this project’s innovative approach has the potential to transform science education by providing teachers with practical tools and strategies to engage students in science and promote a deeper understanding of space-science concepts.